INTEGRATED GEOTECHNICAL AND GEOPHYSICAL INVESTIGATION OF A PROPOSED CONSTRUCTION SITE AT MOWE, SOUTHWESTERN NIGERIA - Oyedele, K. F.; Oladele, S.; Nduka, A. C (GeoScience Engineering, 2018)
The subsurface of a proposed site for building development in Mowe, Nigeria, using Standard Penetration Test (SPT) and Cone Penetrometer Test (CPT) supplemented with Horizontal Electrical Profiling (HEP) was investigated with the aim of evaluating the suitability of the strata for foundation materials. Four SPT and CPT were implemented using 2.5 tonnes hammer. HEP utilizing Wenner array were performed with an inter-electrode spacing of 10 – 60 m along four traverses coincident with each of the SPT and CPT. The HEP data were processed using DIPRO software and textural filtering of the resulting resistivity sections was implemented to enable delineation of hidden layers. Sandy lateritic clay, silty lateritic clay, clay, clayey sand and sand horizons were delineated. The SPT “N” value defined very soft to soft sandy lateritic (<4), stiff silty lateritic clay (7 – 12), very stiff silty clay (12 - 15), clayey sand (15- 20) and sand (27 – 37). Sandy lateritic clay (5-40 kg/cm2) and silty lateritic clay (25 - 65 kg/cm2) were defined from the CPT response. Sandy lateritic clay (220-750 Ωm), clay (< 50 Ωm) and sand (415-5359 Ωm) were delineated from the resistivity sections with two thin layers of silty lateritic clay and clayey sand defined in the texturally filtered resistivity sections. Incompetent clayey materials that are unsuitable for the foundation of the proposed structure underlain the study area to a depth of about 18m. Deep foundation involving piling through the incompetent shallow layers to the competent sand at 20 m depth was recommended. Keywords: Standard Penetration Test, Cone penetrometer, Resistivity Section, Lithologic Texture, Foundation https://doi.org/10.2478/gse-2018-0014